Limited acclimation of early life stages of the coral Seriatopora hystrix from mesophotic depth to shallow reefs - Rian Prasetia; Frederic Sinniger; Takashi Nakamura; Saki Harii (Scientific Reports, 2022)
Abstract Mesophotic coral ecosystems (MCEs, reefs between 30 and 150 m depth) have been hypothesized to contribute to shallow reef recovery through the recruitment of larvae. However, few studies have directly examined this. Here we used mesophotic colonies of Seriatopora hystrix, a depth generalist coral, to investigate the effect of light intensity on larval behavior and settlement through ex situ experiments. We also investigated juvenile survival, growth, and physiological acclimation in situ. Bleached larvae and a significant reduction in settlement rates were found when the mesophotic larvae were exposed to light conditions corresponding to shallow depths (5 and 10 m) ex situ. The in situ experiments showed that mesophotic juveniles survived well at 20 and 40 m, with juveniles in shaded areas surviving longer than three months at 3–5 m during a year of mass bleaching in 2016. Juvenile transplants at 20 m showed a sign of physiological acclimation, which was reflected by a significant decline in maximum quantum yield. These results suggest that light is a significant factor for successful recolonization of depth-generalist corals to shallow reefs. Further, recolonization of shallow reefs may only occur in shaded habitats or potentially through multigenerational recruitments with intermediate depths acting as stepping stones.